2002
DOI: 10.1038/sj.bjp.0704540
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological characterization of the chemokine receptor, CCR5

Abstract: 1 We investigated the e ects of a number of naturally occurring chemokines (MIP-1a, MIP-1b, RANTES, MCP-2, MCP-3, MCP-4) on di erent processes linked to the chemokine receptor CCR5 in recombinant CHO cells expressing the receptor at di erent levels. 2 Internalization of CCR5 following chemokine treatment was studied and MIP-1a, MIP-1b and RANTES (50 nM) were able to induce internalization (*50%) of the receptor. Internalization due to MCP-2, MCP-3 and MCP-4 was less (*20%). 3 Phosphorylation of CCR5 following … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 31 publications
2
40
1
Order By: Relevance
“…Several authors reported the ability of RANTES to mobilize Ca 2ϩ ions in cultured neurons (Bolin et al, 1998;Meucci et al, 1998;Boutet et al, 2001;Oh et al, 2001;Gillard et al, 2002;Mueller et al, 2002;Watson et al, 2005;Ignatov et al, 2006), an observation consistent with release of glutamate evoked by RANTES. The facilitation by RANTES of glutamate release may, by one side, explain the pathogenic effects that the chemokine can produce under some pathological conditions associated with neuroinflammation (i.e., HIV-1 infection, multiple sclerosis), including the regulation of T-cell chemotactic migration in CNS.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Several authors reported the ability of RANTES to mobilize Ca 2ϩ ions in cultured neurons (Bolin et al, 1998;Meucci et al, 1998;Boutet et al, 2001;Oh et al, 2001;Gillard et al, 2002;Mueller et al, 2002;Watson et al, 2005;Ignatov et al, 2006), an observation consistent with release of glutamate evoked by RANTES. The facilitation by RANTES of glutamate release may, by one side, explain the pathogenic effects that the chemokine can produce under some pathological conditions associated with neuroinflammation (i.e., HIV-1 infection, multiple sclerosis), including the regulation of T-cell chemotactic migration in CNS.…”
Section: Discussionmentioning
confidence: 59%
“…Activation of these receptors usually triggers G-protein-coupled PTx-sensitive intracellular pathways, leading to facilitation or inhibition of cellular responses (Zhao et al, 1998;Klein et al, 1999;Boutet et al, 2001;Mueller et al, 2002). Because the effects of hRANTES on [ 3 H]D-ASP release are PTx sensitive, CCR1, CCR3, and CCR5 might have mediated the observed effects on basal and depolarization-evoked release.…”
Section: Effects Of Hrantes On the Release Of [ 3 H]d-asp From Human mentioning
confidence: 99%
“…This observation is consistent with clinical studies showing that almost complete CCR5 occupancy is required to significantly reduce plasma viremia (29) and suggests that only a few unoccupied receptors may be sufficient to initiate and sustain a spreading infection. However, as with human CCR5, rhesus CCR5 was not fully internalized by MIP-1␤ in PBMCs or rectal leukocytes in the in vitro assay, thus limiting our analysis to the proportion of CCR5 that was downregulated by MIP-1␤ ex vivo (31). Also, our analysis of MVC binding to rectal CCR5 was performed in SHIV-infected macaques, which might have overestimated occupancy since the number of high CCR5-expressing activated memory CD4 ϩ T cells are expected to be significantly reduced with SHIV infection (39).…”
Section: Discussionmentioning
confidence: 99%
“…[ 35 (28,29). Briefly, 7 g of cell membranes were preincubated with 40 M GDP (Sigma) in the absence (basal binding) or presence of an agonist for 30 min at 30°C before addition of [ Calcium Mobilization-CHO cells were loaded with 2 g/ml fura-2 acetoxymethyl ester (Molecular Probes).…”
Section: Methodsmentioning
confidence: 99%